Perceptions of social interactions and second language willingness to communicate in different activities - He Han; Bing Li (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract This study examined whether students’ perceived social interactions within different learning activities predicted their willingness to communicate (WTC) in second language (L2) classrooms. The sample was 932 undergraduate students from 8 universities learning English as a foreign language. Data of student-perceived social interactions in classrooms including teacher-student relationships, peer relationships, cooperation and equity, and data of WTC including overall WTC, WTC in meaning-focused activities, and WTC in form-focused activities were collected through online questionnaires. Data analysis using Structural Equation Modelling showed that (1) teacher-student relationships, peer relationships and cooperation positively predicted overall WTC; (2) teacher-student relationships, peer relationships, cooperation and equity positively predicted WTC in meaning-focused activities; (3) cooperation positively but equity negatively predicted WTC in form-focused activities. The results suggested that students’ perceived social interactions had predictive effects on L2 WTC but such effects differed in line with learning activity types. Implications for enhancing WTC in L2 instruction were also discussed.